2018
DOI: 10.2139/ssrn.3111466
|View full text |Cite
|
Sign up to set email alerts
|

Do Rewards Encourage Professional Skepticism?

Abstract: It is an open question whether auditors have credible incentives to exercise professional skepticism. We focus on costly skepticism: skepticism that is appropriate and generates incremental costs, but does not identify a misstatement. Costly skepticism is typically not rewarded by audit supervisors. We theorize and find that rewarding costly skepticism may backfire and decrease skepticism on subsequent audit tasks where evidential red flags are present. We reason that auditors interpret the reward as a non-cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…One concern over the use of data analytics is the likelihood of false positives, or the extent that these tools identify transactions or relationships as potential anomalies that, after further investigation, are determined to be reasonable, explained variations in the data (AICPA [2017], Baadder and Krcmar [2018], Johnson and Wiley [2019], Austin et al [2019], Brazel, Leiby, and Schaefer [2020], Arens et al [2020]). 1 The frequency of false positives increases proportionately with the size and complexity of the data analyzed (Krahel and Titera [2015], Kogan, Mayhew, and Vasarhelyi [2019]).…”
Section: Introductionmentioning
confidence: 99%
“…One concern over the use of data analytics is the likelihood of false positives, or the extent that these tools identify transactions or relationships as potential anomalies that, after further investigation, are determined to be reasonable, explained variations in the data (AICPA [2017], Baadder and Krcmar [2018], Johnson and Wiley [2019], Austin et al [2019], Brazel, Leiby, and Schaefer [2020], Arens et al [2020]). 1 The frequency of false positives increases proportionately with the size and complexity of the data analyzed (Krahel and Titera [2015], Kogan, Mayhew, and Vasarhelyi [2019]).…”
Section: Introductionmentioning
confidence: 99%
“…3 In other words, performance evaluations may incentivize some auditors to not exercise heightened skepticism, since auditors often feel that their procedures are not likely to uncover misstatements or problems (Carlisle, Gimbar, and Jenkins 2019). Brazel et al (2019b) further find that incentives for auditor skepticism must be consistent to be credible. One worrisome implication of research is that auditors may be "trained" early in their careers to not follow the evidence and not behave in a professionally skeptical manner.…”
Section: Question-specific Commentarymentioning
confidence: 92%
“…Still other research suggests that audit staff who are "quality minded" and exercise greater professional skepticism may not be rewarded for their efforts, but instead may receive a poor performance evaluation (Brazel et al 2016;Brazel, Gimbar, Maksymov, and Schaefer 2019a;Brazel, Leiby, and Schaefer 2019b). 3 In other words, performance evaluations may incentivize some auditors to not exercise heightened skepticism, since auditors often feel that their procedures are not likely to uncover misstatements or problems (Carlisle, Gimbar, and Jenkins 2019).…”
Section: Question-specific Commentarymentioning
confidence: 99%
“…Academic research has demonstrated the importance and impact of an audit firm's culture on the exercise of professional skepticism (e.g., Gold, Gronewold, and Salterio 2014;Brazel et al 2016;Brazel, Leiby, and Schaefer 2019). To highlight this connection, we suggest adding language to paragraph 7 that describes that the engagement partner's responsibility is not only to demonstrate the appropriate exercise of professional skepticism, but also to create a culture among all engagement team members that encourages and facilitates the exercise of skepticism.…”
Section: Question-specific Commentarymentioning
confidence: 99%